(3GdeRGQYs - (3CHj SYjO(B, (3GdOjhgLjs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2002)
(3GdEYJHGQGJ GdeJYdbI HGdeMGUjd GdRQGYjI(B-(3ENJjGQ GdCQV GdRQGYjI(B-(3eHGOF JbQjQ cjajI GdadGMI hfhYjI GdeMGUjd(B-(3GdeYGdLGJ GdRQGYjI hGdNRf hGdJShjb(B-(3Tcd hJNWjW GdeRQYI(B-(3UZGQ GdadGMjf hGdYeGdI(B-(3GdYeGdI hEOGQJgG aj GdeRGQY GdcHjQI(B-(3GdcaGAI aj GdRQGYI(B-(3GdEYJHGQGJ GdeJYdbI HGdeMGUjd GdfHGJjI(B-(3GdJehjd hGdMSGHGJ GdeRQYjI(B-(3fbGW egeI aj EOGQI bWjY GdehGTjs
Keywords: (3GdRQGYI(B- (3GbJUGOjGJs; (3GdadGMIs; (3GdeRGQY(B-(3JfXje h GOGQIs